DEVELOPMENT OF A REFLECTIVE COMPONENT OF FUTURE TEACHER’S READINESS TO WORK WITH GIFTED CHILDREN DURING TRAINING - Demchenko, Оlena; Koval, Tatiana; Vatso, Mykhailo; Lymar, Yulia; Turchyna, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The necessity of special training of future teachers to work with gifted children is substantiated. In the article defined innovative approaches to improving the educational process in a pedagogical university have been determined in order to create conditions for students to acquire the qualities necessary for the identification of gifted children and to create favorable conditions for their creative self-realization. The importance of reflective abilities in the structure of future teacher’s readiness to work with gifted children is shown. The results of diagnostics of students reflexive abilities are presented, the insufficient level of their formation is revealed. The importance of training in the development of future teachers of the reflective component of readiness to work with children is shown. The experience of conducting trainings, which were developed and tested within the framework of the international project «Development of a culture of democracy in teacher education in Norway, Ukraine and Palestine», is presented. Examples of reflexive training exercises are given, the implementation of which will contribute to the development of future teachers ability to professional self-examination and self-esteem.